Korelasi antara Hadis Larangan Risywah dan Hadiyat al-'Ummal dengan Undang-Undang Negara Republik Indonesia terkait Pelarangan Suap Menyuap dan Gratifikasi dalam Menjaga Stabilitas Ekonomi Negara - Aufi Izzadine; Nur Kholis bin Kurdian (AL-ATSAR: Jurnal Ilmu Hadits, 2023)
Risywah (bribery) and hadiyat al-‘Ummal (gratification) have become a common practice in some developing countries. Therefore, to anticipate such incidents, the government in our country has issued laws prohibiting the giving of tips, gifts, and the like to officials or state officials related to their work. This is stated in the hadith of the Prophet Muhammad shallallahu ‘alaihi wasallam specifically in the prohibition of giving and receiving bribery and gratuities. This study discusses the relationship between these hadiths and Indonesian laws related to the prohibition of giving and receiving bribery and gratuities. The purpose of this research is: (1) To find the correlation or relationship between Islamic teachings and laws that regulate the acceptance of bribery and gratuities in the context of law and morality, (2) To analyze the impact of accepting bribery and gratuities on the country's economic stability, thus providing further understanding of the importance of combating bribery and gratuities in the country's economic development and preventing losses for society. The methodology of this research is qualitative, using a literature review approach and referring to the opinions of experts in the field through classic and contemporary literature, online newspapers, social media, and interviews if needed. The results of this research are as follows: (1) The prohibition of giving and receiving bribes and gratuities is an important principle in Islam and is also emphasized in the laws of Indonesia. (2) The correlation between the hadith prohibiting bribery and hadiyat al-'Ummal with the laws on accepting bribes and gratuities is that both legal sources have the same purpose as the law, which is to prohibit corrupt practices and provide sanctions for the perpetrators. (3) Bribes and gratuities have an impact on the economic growth of the country.